Microwave Irradiation Assisted Preparation of Chitosan Composite Microsphere for Dye Adsorption. (2nd January 2017) - Chen, Xiaoyu; He, Lindun
Abstract : Chitosan-activated carbon composite microspheres were prepared by emulsion cross-linking method and its adsorption properties for methyl orange were studied. Chitosan solution was mixed with activated carbon powder and then chitosan was cross-linked by epichlorohydrin under microwave irradiation. SEM photos show that the composite microspheres have diameters of 200–400 μ m and activated carbon powder dispersed on the surface of composite microsphere. FTIR spectrum indicates chitosan is successfully cross-linked. Microwave irradiation can effectively shorten the cross-linking time. Composite microspheres have enhanced dye adsorption capacity for methyl orange compared to chitosan microspheres. Kinetic studies showed that the adsorption followed a pseudo-second-order model. Isotherm studies show that the isotherm adsorption equilibrium is better described by Freundlich isotherm. Regeneration results show that adsorption capacity of composite microsphere decreased about 5.51% after being reused for three times. These results indicated that chitosan-activated carbon composite microsphere has potential application in the removal of dye from wastewaters.